Delayed Endovascular Coil Extrusion following Internal Carotid Artery Embolization - Dedmon, Matthew (J Neurol Surg Rep, 2014)
Internal carotid artery injury is a rare and devastating complication of endoscopic sinus and skull base surgery that has an associated mortality rate of 15%. This case describes a patient who developed massive epistaxis following routine sinus surgery and was eventually diagnosed with a pseudoaneurysm of the cavernous internal carotid artery. Endovascular coiling and Onyx (Covidien, Irvine, California, United States) liquid embolization were ultimately used to completely occlude the internal carotid artery with resolution of bleeding; however, the patient had an unexpected late complication of coil extrusion through the pseudoaneurysm sac into the sphenoid sinus and nasal cavity. The endoscopic skull base team safely excised the coils endoscopically without recurrent bleeding. We describe the multidisciplinary operative management of this case of endovascular coil extrusion to increase awareness of this potentially life-threatening complication.